(untitled) (Collection of scientific works «Modern structures of metal and wood», 2019)
This article deals with the study of parameters of the stress-strain state of the elements of conical roofs of the cylindrical silos. They are mainly made of the thin sheet steel structures. On the basis of the finite element method modern design and calculation complexes of the strength analysis allow easily and with sufficient accuracy perform such a calculation. However, in some cases there are such problems when using a computerized data-entry machine rather complicates the decision process. The alternative is to solve this problem in a simple form of analytical calculation. Though the result will have less accuracy, but it will significantly reduce both time and work load of a designer. This article considers a number of practical questions that occur in case of a constructive solution of the main radial rib of the roof in the form of a beam of the thin- walled profile or a construction with parallel belts. In the calculation scheme of the rib it was illustrated the features of considering the presence of three annular stiffeners and secondary beams. It was proposed a simplified procedure for estimating current loads, by replacing four sections of unevenly distributed load with one of equivalent action. The search of unknown internal forces in this calculation scheme is performed by the force method. The general algorithm lies in a consistent determination of efforts in the main radial rib from the single efforts; in calculation of parameters of equivalently distributed load; in finding the effort functions of the given load and thermal suspension, as well as of the pressure of the annular stiffeners; in determining the horizontal displacements of points of disconnection in the main system and the magnitude of the displacements; in calculation of unknown support reactions and determination of internal efforts for dangerous sections. The numerical implementation allows estimating the accuracy of this calculation. Also the example demonstrates the simplicity of its implementation, compared to a computer procedure based on the finite element method.